Pengembangan Media E-Flip Modul Berbasis Web Pada Materi Interaksi Makhluk Hidup Dengan Lingkungan Untuk Siswa Kelas VII MTS AL-AMIN - Khoirun Nisa; Binti Basruroh; Metatia Intan Mauliana; Nisfil Maghfiroh Meita (IKIP Budi Utomo Malang, 2022)
This study aims to develop a web-based e-module learning media on interactions of Living things for class VII students at Mts. Al-Amin. In this development research using the 4D development model, namely define, design, develop, and disseminate. However, in this research the stages are only up to develop (development). In the material validation test, an assessment of 92.5% was obtained with a very feasible category, in the media validation assessment, a value of 93.9% was obtained with a very feasible category. After validating media experts, there was a readability test conducted by students at Mts. Al-Amin, numbering 20 people. By obtaining a value of 91.6% in the very good category. Based on the results of the assessment data that has been carried out the development of web-based e-module learning media is declared to meet the criteria of very feasible and very good for use as learning